The Ways of Penetration of Words from Western Armenian to Eastern Armenian - MELKONYAN, LUIZA (Bulletin of Yerevan University B: Philology, 2021)
Borrowing is the main outer way of stocking of lexical fund of the language. But there also exists an inner borrowing, which isconsidered to be one of the inner ways of word stock enrichment. Social changes also had their impact on the literary Eastern-Armenian language, especially on the word stock of the language. Depending upon different conditions, the word stock of Eastern-Armenian language was penetrated by many West-Armenian words, which came to name new concepts and phenomena or to replace foreign word units. These words must be represented by different groups:1. Words penetrated from West-Armenian, which are absolutely new in East- Armenian literary language, i.e. they are not registered in “Explanatory dictionary of modern Armenian” of E. Aghayan and in a four-volume “Explanatory dictionary ofmodern Armenian Language” published by AC (Academy of Sciences). From this we come to a conclusion, that these are mainly recent borrowings.2. Words that are registered in “Explanatory dictionary of modern Armenian” of Aghayan by the link ³ñ¨Ùï. (Western Armenian). These are the words, which in Western-Armenian are known exceptionally as Eastern-Armenian words and which had not been used in Western Armenian.
Keywords: borrowings, Western-Armenian language, semantic neologisms, terms, vocabulary, linguistic interactions, semantic alteration